PENGEMBANGAN MEDIA SCRAPBOOK PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS IV SEKOLAH DASAR - Widya, Widya; Putri Ami, Weni (Jurnal Riset Pendidikan Dasar Dan Karakter, 2024)
This study was motivated by the use of learning media that is still limited to printed textbooks and lacks the use of concrete media. The aim of this research is to develop a scrapbook learning media for Theme 2 “Always Save Energy”, Sub-theme 1 "Sources of Energy", Lesson 1 for Grade IV of elementary school. The research used a Research and Development (R&D) method with the 4-D model (define, design, develop, disseminate). Instruments used included concept and learning objective analysis sheets, validity and practicality questionnaires, as well as pre-test and post-test questions. Validation was conducted by design, language, and material experts, resulting in a validity score of 95% (very valid). Practicality tests showed scores of 99% from teachers and 91% from students (very practical). The average pre-test score was 50.4, and the post-test score was 84.5. The t-test showed a significance value of 0.000 < 0.05, indicating H₀ is rejected and Hₐ is accepted. Therefore, the developed scrapbook media is considered valid, practical, and effective in supporting the learning process.